1994
DOI: 10.1128/iai.62.5.2122-2125.1994
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides from Campylobacter jejuni associated with Guillain-Barré syndrome patients mimic human gangliosides in structure

Abstract: Lipopolysaccharides extracted from Campylobacter jejuni serostrains (serotype reference strains) for serotypes 0:4 and 0:19 were found to have core oligosaccharides with terminal structures resembling human gangliosides GM, and GD1a. High-molecular-weight molecules that reflected the presence of 0 chains were shown in immunoblots to be immunologically specific for each serostrain. The 0:19 antiserum also reacted strongly with core oligosaccharides of two isolates from patients with Guillain-Barre syndrome (GBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(83 citation statements)
references
References 16 publications
2
78
1
2
Order By: Relevance
“…Molecular mimicry between C. jejuni lipo-oligosaccharide (LOS) and GM1 ganglioside has been established as one of the disease mechanisms of GBS. 2,15 In our patient, acute polyradiculoneuropathy was confirmed by clinical examination and electrophysiological studies, and high titers of anti-GM1 (IgG and IgM) antibodies further supported the diagnosis. Other antibodies, such as anti-GD1a, anti-GD1b, and anti-GQ1b, were not examined.…”
Section: Discussionsupporting
confidence: 67%
“…Molecular mimicry between C. jejuni lipo-oligosaccharide (LOS) and GM1 ganglioside has been established as one of the disease mechanisms of GBS. 2,15 In our patient, acute polyradiculoneuropathy was confirmed by clinical examination and electrophysiological studies, and high titers of anti-GM1 (IgG and IgM) antibodies further supported the diagnosis. Other antibodies, such as anti-GD1a, anti-GD1b, and anti-GQ1b, were not examined.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, there is mounting evidence suggesting that lipopolysaccharide (LPS) on the outer core of the bacteria can mimic host gangliosides. LPS from C. jejuni serotypes associated with GBS were shown to resemble human gangliosides structurally [187,188], and priming of mice, rats and rabbits with the above-mentioned LPS produced corresponding anti-ganglioside antibodies [189][190][191]. Several studies have shown that C. jejuni serotypes associated with GBS are more likely to contain ganglioside-like epitopes compared with serotypes isolated from C. jejuni-infected patients with gastroenteritis but no neurological symptoms, with one study linking ganglioside mimicry to specific GBS clinical subtypes [192,193].…”
Section: Guillain-barré Syndromementioning
confidence: 99%
“…Several studies have suggested that immune recognition of cross-reacting epitopes on antigens common to C. jejuni and peripheral nerve myelin might provide a possible mechanism by which an autoreactive response leads to demyelination [1,4]. Support for a such an autoimmune etiology comes from recent reports of structural similarity between the lipopolysaccharide (LPS) of C. jejuni strains isolated from GBS patients and the peripheral nerve gangliosides GM1, GQ1b and GD1a [5,6]. Antibodies to these gangliosides, present in about 30% of GBS patients, have also been found to show cross-reactivity to C. jejuni LPS [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Support for a such an autoimmune etiology comes from recent reports of structural similarity between the lipopolysaccharide (LPS) of C. jejuni strains isolated from GBS patients and the peripheral nerve gangliosides GM1, GQ1b and GD1a [5,6]. Antibodies to these gangliosides, present in about 30% of GBS patients, have also been found to show cross-reactivity to C. jejuni LPS [5,6].…”
Section: Introductionmentioning
confidence: 99%